2005
DOI: 10.4269/ajtmh.2005.73.1038
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Serosurveillance in Iowa White-Tailed Deer (1999–2003)

Abstract: Sera from white-tailed deer (Odocoileus virginianus) were collected in Iowa during the winter months (1999-2003), 2 years before and after West Nile virus (WNV) was first reported in Iowa (2001), and were analyzed for antibodies to WNV. Samples from 1999 to 2001 were antibody negative by blocking enzyme-linked immunosorbent assay (bELISA) and plaque reduction neutralization test (PRNT(90)). Prevalence derived from bELISA (2002, 12.7%; 2003, 11.2%) and WNV PRNT(90) (2002, 7.9%; 2003, 8.5%) assays were similar. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…Similar seroprevalences were also found in white-tailed deer in the United States [22, 23]. In contrast, a limited number of wild ruminants from south-western Spain tested during surveillance of WNV outbreaks were negative for flavivirus antibodies using the same bELISA [8].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Similar seroprevalences were also found in white-tailed deer in the United States [22, 23]. In contrast, a limited number of wild ruminants from south-western Spain tested during surveillance of WNV outbreaks were negative for flavivirus antibodies using the same bELISA [8].…”
Section: Discussionmentioning
confidence: 61%
“…Antibodies against St. Louis encephalitis virus (SLEV) and WNV have been found in white-tailed deer ( Odocoileus virginianus ) from the United States [22, 23], and against TBEV and WNV in different game species from the Czech Republic [24]. In addition, fatal cases of WN fever were reported in white-tailed deer and reindeer ( Rangifer tarandus ) in North America [25, 26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature, we expected similar seropositivity rates in deer and wild boar (Santaella et al 2005;Halouzka et al 2008). However, free-living juvenile wild boar appeared to be far more suitable as sentinels than free-living juvenile red deer.…”
Section: Discussionmentioning
confidence: 80%
“…Studies in white-tailed deer (Odocoileus virginianus) demonstrated that it is unlikely that they are an important amplifying host for WNV (Farajollahi et al 2004), but that clinical disease and mortality are possible (one fatal case was described by Miller and associates [2005]). Several authors demonstrated seroconversion with enzyme-linked immunosorbent assays (ELISA), and by plaque-reduction neutralization tests (PNRT), and prevalences obtained ranged 0.9-12.7% (Farajollahi et al 2004;Santaella et al 2005). Regarding the Eurasian wild boar (Sus scrofa), we assume an analogous response to that of domestic pigs (Sus scrofa).…”
Section: Vector-borne and Zoonotic Diseasesmentioning
confidence: 93%